ΓΥΡΩ ΑΠΟ ΤΟΝ ΑΛΕΞΑΝΔΡΟ ΗΣΑΪΑ ΚΑΙ ΤΙΣ ΛΙΘΟΓΡΑΦΙΕΣ ΤΟΥ. ΠΡΟΣΘΗΚΗ (βλ. σ. 135-143) - ΛΑΠΠΑΣ, ΚΩΣΤΑΣ (Μνήμων, 1979)
<span style="font-size: 10.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EL; mso-fareast-language: EL; mso-bidi-language: AR-SA;">No abstract.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->